Evaluasi Pengendalian Persediaan Terhadap Hasil Stock Opname Melalui Sistem Informasi Akuntansi Pada Gota Minimarket - Zulafa Arianty, Gabinda Zahra; Zahra, Gabinda; Supriadi, Iman (Jurnal Akuntansi, Manajemen, Bisnis dan Teknologi, 2021)
This study aims to evaluate inventory control on the results of stock opname through the Accounting Information System and to analyze the causes of the difference in stock at Gota Minimarket. In this study using a descriptive qualitative method with a case study approach to describe inventory control of the results of stock opname through the Accounting Information System. The primary data source is obtained by conducting interviews with managers, purchase order admins, goods receiving officers, and area coordinators. Meanwhile, secondary data is obtained through documentation, trough data collection related to merchandise inventory. The Accounting Information System applied by Gota Minimarket in controlling inventory is good enough. This is evident from all activities in its operations, in terms of ordering and purchasing goods, receiving goods, inputting goods, requesting goods to the mutation of warehouse goods that have been carried out through the Information System.However, employee negligence often occurs, causing a difference in stock opname.